Waterbird conflicts in Britain and Ireland: Ruddy Ducks Oxyura jamaicensis, Canada Geese Branta canadensis, and Cormorants Phalacrocorax carbo - Hughes, B; Kirby, J; Rowcliffe, J M (Wildfowl, 1999)
Conflict between waterbirds and man has been reported in the UK since the seventh century. During the last two decades, attention has focussed on damage to agriculture and amenity land, and more recently depredation of fish stocks, and the impacts of introduced waterfowl. The Canada Goose and Ruddy Duck are both non-native species introduced into the UK from North America in the 17th and 20th centuries, respectively, whilst the Cormorant is a native seabird which has extended its range inland. Increasing populations of all three species have recently created conflict situations: the Ruddy Duck through emigrating to the continent and hybridising with the White-headed Duck, the Canada Goose mainly through damage to amenity grassland, and the Cormorant through depredation of fish stocks. This paper reviews the impact of these species on biodiversity and human interests, provides information on population trends and distribution, and highlights how UK management strategies have been based on sound science.